Contributions of nursing care in the normal birth center for obstetric and neonatal care (Research, Society and Development, 2020)
Analyze the scientific evidence about the contributions of nursing care in the normal birth center to obstetric and neonatal care. The present study deals with a bibliographic review of the integrative literature review method, carried out in November 2020. The search was carried out, through the - VHL, using the databases LILACS, BDENF, and through from the Google Scholar Portal, adhering to the descriptors: “Nursing care” AND “Normal Delivery Center” AND “Obstetric Care”, crossed with the operator by typing “AND”. The role of nurses in assisting women in the parturition process is currently considered a possibility for reducing maternal and perinatal morbidity and mortality. With this assistance, you will be able to reduce cesarean-type interventional actions, which are often unnecessary. The ANC features, as a characteristic, alternatives and differentiated reception methods, with the performance of obstetric nursing showing itself to be increasingly concerned with the movement to defend individuality and empower the parturient, thus allowing adaptation of assistance to culture, religion, values and desires of women and family.